Pengaruh Macam Media Tanam dan Lama Pengomposan Terhadap Hasil Jamur Kuping (Auricularia polytricha) - Sumarmi, Sartono Joko Santoso Daru Cahya Sitaresmi (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACT   The purpose of the research to know the effect tkinds of plant medim and the length of time compost to harvest ear mushroom, have been done in Dlimas region, Ceper, Klaten, Central Java from August until September 2006. The research used 3 kinds of plant medium: the powder of teak, durian and sengon wood. The length time of compost are 10, 20 and 30 days, used Completely randomized Design (CRD)  with 3 replication. The parameter observed was the fisrt growing mycelium, mushroom diameter, fresh weight of mushroom, the dry weight of mushroom, and the moisture content of mushroom. Mycelium was rapid grow on the powder of sengon wood dan length composed 10 days. The biggest diameter of mushroom on on the powder of durian wood dan length composed 30 days. The largest  ear mushroom with fresh weight and dry weight was on the powder of sengon wood dan length composed 10 days, and the moisture content of mushroom is largest too. Using the powder of teak wood and durian wood was  not good to medium growth of ear mushroom. Key word: plant medium, composted, ear mushroom